DCET1 Controls Male Sterility Through Callose Regulation, Exine Formation, and Tapetal Programmed Cell Death in Rice - Khan, Riaz Muhammad; Yu, Ping; Sun, Lianping; Abbas, Adil; Shah, Liaqat; Xiang, Xiaojiao; Wang, Dongfei; Sohail, Amir; Zhang, Yingxin; Liu, Qunen; Cheng, Shihua; Cao, Liyong (Frontiers in Genetics, 2021)
In Angiosperms, anther development comprises of various complex and interrelated biological processes, critically needed for pollen viability. The transitory callose layer serves to separate the meiocytes. It helps in primexine formation, while the timely degradation of tapetal cells is essential for the timely callose wall dissolution and pollen wall formation by providing nutrients for pollen growth. In rice many genes have been reported and functionally characterized, involved in callose regulation and pollen wall patterning, including timely programmed cell death (PCD) of the tapetum, but the mechanism of pollen development largely remains ambiguous. We identified and functionally characterized a rice mutant dcet1, having a complete male-sterile phenotype caused by defects in anther callose wall, exine patterning and tapetal PCD. DCET1 belongs to RNA recognition motif (RRM)-containing family also called as ribonucleoprotein (RNP) domain or RNA-binding domain (RBD) protein, having single nucleotide polymorphism (SNP) substitution from G (Threonine-192) to A (Isoleucine-192) located at the fifth exon of LOC_Os08g02330, was responsible for male sterile phenotype in mutant dcet1. Our cytological analysis suggested that DCET1 regulates callose biosynthesis and degradation, pollen exine formation by affecting exine wall patterning, including abnormal nexine, collapsed bacula, irregular tectum, and timely PCD by delaying the tapetal cells degeneration. As a result, the microspore of dcet1 was swollen and abnormally bursted and even collapsed within the anther locule with complete male sterility. GUS and qRT-PCR analysis indicated that DCET1 is specifically expressed in anther till the developmental stage 9, consistent with the observed phenotype. The characterization of DCET1 in callose regulation, pollen wall patterning and tapetal cells PCD strengthens our knowledge for knowing the regulatory pathways involved in rice male reproductive development and has future prospects in hybrid rice breeding.